2012
DOI: 10.1063/1.4754617
|View full text |Cite
|
Sign up to set email alerts
|

Detecting single molecules inside a carbon nanotube to control molecular sequences using inertia trapping phenomenon

Abstract: Here we show the detection of single gas molecules inside a carbon nanotube based on the change in resonance frequency and amplitude associated with the inertia trapping phenomenon. As its direct implication, a method for controlling the sequence of small molecule is then proposed to realize the concept of manoeuvring of matter atom by atom in one dimension. The detection as well as the implication is demonstrated numerically with the molecular dynamics method. It is theoretically assessed that it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In addition to thermal fluctuation, studies confirm that the vibration can also transport particles and droplets in and outside a carbon nanotube (CNT) [ 24 27 ]. For example, the nanodroplets are transported along the nanotube with a velocity close to 30 nm/ns when linearly polarized transverse acoustic waves pass linear momentum to the nanodroplet [ 24 , 28 ]. Guo et al demonstrated that water molecules inside a vibrating cantilever are driven by centrifugal forces and can undergo a continuous flow from the fixed to free ends of the CNT by molecular dynamics simulations [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to thermal fluctuation, studies confirm that the vibration can also transport particles and droplets in and outside a carbon nanotube (CNT) [ 24 27 ]. For example, the nanodroplets are transported along the nanotube with a velocity close to 30 nm/ns when linearly polarized transverse acoustic waves pass linear momentum to the nanodroplet [ 24 , 28 ]. Guo et al demonstrated that water molecules inside a vibrating cantilever are driven by centrifugal forces and can undergo a continuous flow from the fixed to free ends of the CNT by molecular dynamics simulations [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%